PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA AGROINDUSTRI TAHU PADA SENTRA INDUSTRI TAHU DI PEKON GADINGREJO KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Moch Angga Satria; Rabiatul Adawiyah; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study intends to interprete the income, the level of household welfare of tofu agroindustry owners and to know the factors related to the level of household welfare of tofu agroindustry owners at the tofu industry center, Gadingrejo District, Pringsewu Regency. The research location is in Pekon Gadingrejo, Gadingrejo District, Pringsewu Regency using a census method. There are 15 respondents who own tofu agroindustry in Pekon Gadingrejo. Data analysis uses a descriptive quantitative analysis that includes the level of welfare according to Sajogyo, BPS, World Bank, and ADB as well as Spearman Rank analysis to determine the related factors. The results showed that the household income of tofu agroindustry owners in Pekon Gadingrejo was before the pandemic of IDR32,214,381.20 per month with a percentage of 97,41% of tofu agroindustry businesses, and income from other businesses of 2,59%. Household income during the pandemic was IDR23,273,759.10 per month with a percentage of 96,63% of tofu agroindustry businesses and income from other businesses of 3,37%. The welfare and poverty level of tofu agroindustry households in Pekon Gadingrejo based on Sajogyo's criteria, most of the group is sufficient, based on the standard of BPS, which is 40 % in the poor category, based on the criteria of the World Bank and ADB, which is a poverty rate of 0 %. The factors related to the level of household welfare of the tofu agroindustry are the level of household income and household expenditure. Key words:  household, income, tofu, welfare